2016
DOI: 10.1007/s40894-016-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Adolescent Sexual Communication and Adolescents’ Sexual Behaviors: A Conceptual Model and Systematic Review

Abstract: Parent-adolescent sexual communication can help reduce sexual risk behaviors among adolescents. However, research and theory are less clear regarding the specific pathways (i.e., mechanisms of change) by which this communication works to reduce sexual risk behavior. The current review addresses this gap by proposing a conceptual model describing the processes by which parent-adolescent sexual communication influences adolescents' sexual intentions and behaviors and by conducting a systematic review to locate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 55 publications
(134 reference statements)
3
53
1
5
Order By: Relevance
“…Adolescents may not be able to discern accurate from inaccurate information or safe or unsafe practices [30]. Communication with parents and more highly educated mothers was positively associated with attitudes towards safe abortion and confirms the importance of parent-adolescent communication regarding sexuality, reproductive health and skills development [32][33][34][35]. The study also affirms adolescents with sexual experience tend to hold more positive attitudes towards abortion [11,16,30].…”
Section: Interpretationssupporting
confidence: 52%
See 2 more Smart Citations
“…Adolescents may not be able to discern accurate from inaccurate information or safe or unsafe practices [30]. Communication with parents and more highly educated mothers was positively associated with attitudes towards safe abortion and confirms the importance of parent-adolescent communication regarding sexuality, reproductive health and skills development [32][33][34][35]. The study also affirms adolescents with sexual experience tend to hold more positive attitudes towards abortion [11,16,30].…”
Section: Interpretationssupporting
confidence: 52%
“…Comprehensive sexual and reproductive health education should also be included earlier in the school curricula. The importance of parents being involved in discussions with adolescents should not be understated [30,34]. Many parents however may find sexual conversations with adolescents uncomfortable and healthcare workers or other professionals may be able to help parents develop effective strategies for having sexual conversations with their adolescent children [34].…”
Section: Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed factors associated with higher knowledge of safe sex were living with people other than parents, studying family planning and belonging to a religion that accepted the use of birth control. While parents may be an important source of information on sexual and reproductive health at some stages of adolescence, living more independently may reflect other opportunities for gaining knowledge and experience in these matters [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of cultural and societal beliefs and values are emphasized as a key ecological factor in adolescents' risky sexual behaviors [9,18,[30][31][32]. A Thai study [14,33] reported competing influences between traditional parental disapproval and access to western-based pornographic media to be associated with pre-coital behavior, the age of sexual debut and refusal self-efficacy.…”
Section: Introductionmentioning
confidence: 99%